2017
DOI: 10.1111/jcom.12333
|View full text |Cite
|
Sign up to set email alerts
|

YouTube for Good: A Content Analysis and Examination of Elicitors of Self-Transcendent Media

Abstract: Despite the increased attention to eudaimonic media experiences, to date scholars have paid little attention to the specific portrayals responsible for those experiences. Study 1 of this project reports the first systematic content analysis of self-transcendent media-a particular type of eudaimonic media-using a sample of 100 "inspirational" YouTube videos. The presence of 20 specific elicitors associated with self-transcendent emotions was examined and reported. In Study 2, respondents provided real-time self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 26 publications
5
85
0
2
Order By: Relevance
“…----Insert Table 1 here----To explore the co-presence of elicitors (RQ1b), we first summed the direct and modeled elicitors within each of the four conceptual groupings (following the analyses of Dale et al, 2017b). Doing so allows us to gain a better understanding of the kinds of elicitors that may appear in tandem in Facebook posts.…”
Section: Study 1 Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…----Insert Table 1 here----To explore the co-presence of elicitors (RQ1b), we first summed the direct and modeled elicitors within each of the four conceptual groupings (following the analyses of Dale et al, 2017b). Doing so allows us to gain a better understanding of the kinds of elicitors that may appear in tandem in Facebook posts.…”
Section: Study 1 Resultsmentioning
confidence: 99%
“…The coding system for this analysis was developed by Dale and her colleagues (2017b), based on the discussion of self-transcendent emotions and trait transcendence in Peterson and Seligman (2004), which identifies four behavioral manifestations of transcendence: appreciation of beauty and excellence, gratitude, hope, and religiousness/spirituality. Previous research has shown that online media content contains depictions of known elicitors of these behavioral manifestations as well as portrayals of individuals enacting these behaviors (Dale et al, 2017b). The first of these two portrayals, the known elicitors, are referred to as direct elicitors and consist of elicitors that can inspire selftranscendent emotions.…”
Section: Study 1 Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to their definition, being moved can be regarded as a mixed emotion predicting enjoyment of aesthetic stimuli. Being moved as related to media enjoyment has sometimes been characterized as belonging to the class of self-transcendent emotions (Dale, Raney, Janicke, Sanders, & Oliver, 2017;Oliver et al, 2018;Stellar et al, 2017). According to Stellar et al (2017), self-transcendent emotions are experienced as pleasant, other-oriented, and function to bind individuals together (typical examples include awe, compassion, gratitude, and elevation; see also van Cappellen, Saroglou, Iweins, Piovesana, & Fredrickson, 2013).…”
Section: Definitional Issuesmentioning
confidence: 99%